Penerapan Mesin Cetak Otomatis Untuk Meningkatkan Kapasitas Produksi Paku Sekerup Peti Mati Pada UKM Di Surabaya - Siswadi Siswadi; Yuyun Widiastuti; Sandhy PR (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
The manufacturing process of the nail screw coffin UKM still uses a non-permanent manual system molding using printed sand from the Madura area. Meanwhile, the furnace still uses bricks covered with soil mud. so that the production capacity is relatively very low. In order to solve this problem, the executor will: 1) Design, make a coffin screw molding machine and make a furnace from refractory stone by applying Appropriate Technology (TTG) and 2) Provide Marketing management application so that both SMEs understand good marketing management . This has an impact on increasing productivity in UD.Trio Logam and UD. Sinar Logam's nail screw nails UKM, has an impact on the coffin screw of UD Sinar Logam. It is hoped that through this molding machine the output produced can help increase productivity and also affect the welfare of SMEs. The results of the implementation of this community service: 1) This coffin screw nail molding machine and fireproof stone casting furnace can speed up the manufacturing process with good quality. 2) This coffin screw nail molding machine can increase partner productivity to 3 times, from the previous yield of only 45 units per day, will be 135 units per day. 3) The resulting output is of higher quality, 4) lightens the workload because human power is replaced by machines.